HUBUNGAN KATA YAHUDI DAN ISRAIL DALAM AL-QUR'AN (Studi Tafsir Al-Azhar Hamka) - Muhammad, Imaduddin; Abror, Indal (el-Umdah, 2024)
Recently, Israel has become a major topic of public discussion due to the renewed conflict with Palestine that has been ongoing for approximately 76 years. The Qur'an, as the holy book of Islam, mentions the words "Jews" and "Israel" in numerous verses and chapters. As one of the many subjects addressed in the Qur'an, the terms "Jews" and "Israel" form an inseparable unity, even though they have distinct and different meanings. In this paper, Hamka's Tafsir Al-Azhar serves as the primary reference for examining the terms "Jews" and "Israel" in the Qur'an. In line with Tafsir Al-Azhar as the reference, this paper specifically aims to answer three questions: (1) What are the differences between the terms "Jews" and "Israel" in Tafsir Al-Azhar? (2) How does Hamka describe the characteristics of the verses regarding Jews and Israel in Tafsir Al-Azhar? (3) How do the terms "Jews" and "Israel" in Tafsir Al-Azhar relate to recent phenomena? This research is a library study, employing thematic methods. The primary data source is Hamka's Tafsir Al-Azhar, while secondary sources include books, journals, videos, and discourses related to the topic. The research concludes that the term "Jews" is mentioned nine times in the Qur'an. The characteristics of the Jews in Tafsir Al-Azhar include claiming to be the children and beloved of Allah, lying about Allah, believing they are the most righteous, altering the scriptures, demeaning other nations, and hating Muslims. "Israel" is mentioned 42 times in the Qur'an. The characteristics of Israel in Tafsir Al-Azhar include being granted many blessings by Allah, the covenant between Israel and Allah, Israel with the prophets, Israel and Pharaoh, and the traits and behaviors of Israel within society.